The Effect of Economic Growth, Education, Unemployment, and Human Development Index on Poverty in the Special Region of Yogyakarta for Period 2015-2021: Development economy - Suci, Lestari Etika; Addainuri, Muhammad Isbad; Abidin, Maulana (Jurnal Ilmu Ekonomi Terapan, 2023)
This study aims to analyze the impact of economic growth, education, unemployment, and HDI on poverty in the Special Region of Yogyakarta (DIY) Province during 2015-2021. This study uses panel data linear regression analysis using data from five districts/cities in DIY Province. The Central Bureau of Statistics website was the source of information. The analysis techniques used include a model selection test, stationarity or unit root test, classical assumption test, panel data regression analysis, and hypothesis testing using a trial and coefficient of determination (R2) test. The research findings show that economic growth, education, and unemployment do not significantly affect poverty. In contrast, the Human Development Index shows a significant effect on poverty.